2021
DOI: 10.1007/s10668-021-01880-5
|View full text |Cite
|
Sign up to set email alerts
|

Review and synthesis of climate change studies in the Himalayan region

Abstract: There are a few regions in the world, where climate change impacts are more intense than other regions of the world, and Himalaya is the case. The Himalaya, one of the biodiversity hotspot regions and provider of ecosystem services to billion of people all across the world. Present study reviewed and synthesized climate change studies in the Himalayan region in general and Indian Himalayan region (IHR) in particular. Analysis of the literature indicates exponentially increase in climate change studies 2005 onw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 194 publications
0
8
0
Order By: Relevance
“…Trends in warming of mountain surface air temperatures become more and more apparent (López-Moreno et al, 2008;Niedrist et al, 2018;Niedrist and Füreder, 2021), and high-latitude mountains are projected to warm much faster than temperate and tropical mountains (Negi et al, 2021;Nogues-Bravo et al, 2007). Further, warming is accentuated at higher altitudes (Pepin et al, 2015).…”
Section: Climate Change In Mountainsmentioning
confidence: 99%
“…Trends in warming of mountain surface air temperatures become more and more apparent (López-Moreno et al, 2008;Niedrist et al, 2018;Niedrist and Füreder, 2021), and high-latitude mountains are projected to warm much faster than temperate and tropical mountains (Negi et al, 2021;Nogues-Bravo et al, 2007). Further, warming is accentuated at higher altitudes (Pepin et al, 2015).…”
Section: Climate Change In Mountainsmentioning
confidence: 99%
“…Studies by (LI et al 2019;Negi et al 2021;Pramod et al 2023) have suggested that the mountains on the southern slope of the study area experience higher temperatures and precipitation compared to the northern slope. This indicates that the southern slope provides a sheltered environment to resist extreme cold conditions, which may be related to the diverse climate types in this region (Hu and Wei 2022).…”
Section: Discussionmentioning
confidence: 87%
“…However, the Himalayan ecosystems are highly vulnerable and are degrading due to various biotic and abiotic stresses (Wani et al, 2022). Overall, climate change is a leading cause of ecological changes and biodiversity loss, although species invasions are also one of the important factors contributing to changes in forest productivity and biodiversity loss, especially native and endemic species (Behera et al, 2019;Negi et al, 2021;Wani et al, 2021). Besides these factors, the forests of the Himalayan region are now becoming vulnerable due to increasing anthropogenic disturbances like deforestation, unsustainable fuel wood, timber collection, and agricultural expansion (Negi and Maikhuri, 2017;Thakur et al, 2022).…”
Section: Introductionmentioning
confidence: 99%